Targeted therapy of HER2-negative breast cancer - Schütz, Florian; Domschke, Christoph; Schneeweiss, Andreas (Oncology research and treatment, 2016)
Personalized and targeted treatments are the most discussed topics in oncology. However, how much personalized medicine is standard of care nowadays and how much is part of our hope for a better future? So far, only a few targeted therapies are available in daily practice for the treatment of human epidermal growth factor receptor 2 (HER2)-negative breast cancer. And even for these few targeted agents - besides those targeting the estrogen receptor (ER) for endocrine treatment - thus far, predictive factors are missing. There are many new drugs and strategies under evaluation but, unfortunately, they are being developed without any cross-comparison. What drug will we choose for which patient in the future? Without answering this question oncologists will not be able to individualize treatment. Predictive factors for every new splendid drug are eagerly needed before it comes to an approval.